Pedagogy in a new tonality teacher inquiries on creative tactics, strategies, graphics organizers, and visual journals in the K-12 classroom - SpringerLink (Online Service). (Rotterdam SensePublishers, 2011)
This is a book for teachers, by teachers, from elementary school to university level classrooms. It is about the use of creative instructional strategies in K-12 classroom settings, and the transformations the teachers made in their journeys from being traditional practitioners to ?becoming pedagogical? in their approaches to teaching and learning across the curriculum. Over twenty teachers conducted research in their classrooms on the implementation of creative strategies, tactics, graphics organizers, and visual journals in teaching and learning. They have written their inquiries in a narrative style, informed by various forms of arts based educational research. Their research is approachable and usable by other teachers who are interested in becoming reflective-reflexive practitioners. Many of the strategies, tactics, and graphics organizers are described by Barrie Bennett in his widely used textbook, Beyond Monet: The Artful Science of Instructional Intelligence. However, through their journeys of becoming teacher-learner-researchers, many discovered numerous, creative variations of Bennett?s work as it was implemented in their classrooms. While there are many professional books that provide ideas on collaborative learning and creative teaching approaches, there is very little published research on the efficacy of these concepts in the K-12 classroom. These inquiries provide practical insights into how inspired teachers can conduct research on improving their own practice as well as on greatly improving their students? learning. Thus, this book has widespread interest for teachers and administrators who seek to implement systemic changes in the ways that teachers teach, and children learn, in the 21st century.
Electronic reproduction.
Keywords: Teaching; Education -- Research; Electronic books